2013
DOI: 10.1111/hepr.12222
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent partial splenic embolization with transcatheter arterial chemoembolization for hepatocellular carcinoma can maintain hepatic functional reserve

Abstract: Aim: Hepatocellular carcinoma (HCC) is frequently complicated with cirrhosis, and it is not unusual for treatment options to be limited as a result of pancytopenia due to hypersplenism. Partial splenic embolization (PSE) has been performed for thrombocytopenia resulting from hypersplenism. We studied the efficacy in terms of hepatic functional reserve and safety in patients who underwent concurrent transcatheter arterial chemoembolization (TACE) with PSE for HCC. Methods:The study population consisted of 101 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 12 publications
2
43
0
Order By: Relevance
“…In patients with hepatocellular carcinoma, PSE has been combined with transcatheter arterial chemoembolization (TACE) for promising results. In a comparison of patients treated with TACE and concomitant PSE vs TACE alone, those in the combined treatment cohort demonstrated improvements in platelet counts and hepatic reserve [37] .…”
Section: Hematologic Indicesmentioning
confidence: 99%
“…In patients with hepatocellular carcinoma, PSE has been combined with transcatheter arterial chemoembolization (TACE) for promising results. In a comparison of patients treated with TACE and concomitant PSE vs TACE alone, those in the combined treatment cohort demonstrated improvements in platelet counts and hepatic reserve [37] .…”
Section: Hematologic Indicesmentioning
confidence: 99%
“…However, it was not mentioned whether the hematomas were caused by the low PLT count, poor coagulation function, or poor pressurization at the puncture site. Ishikawa et al (24) performed TACE (n=48) or TACE plus PSE (n=53) in 101 HCC patients with reduced PLT counts. There were no obvious complications after the procedure in either of the two groups, and the PLT count increased significantly after the procedure in the combined therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also indicated that in only 16.3% of the procedures the WBC counts were reduced at 3 days after TACE. The increase in the WBC count following TACE is associated with the postoperative embolism syndrome (24), and a reduction in the WBC count is associated with chemotherapy-induced myelosuppression. In only 3 procedures (0.15%) agranulocytosis developed after TACE, but the WBC counts returned to pre-TACE levels following G-CSF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sharp decrease in the levels of WBCs and PLTs caused by hypersplenism raises the incidence of infection and hemorrhage, and secondly, chemotherapy or radiation therapy occasionally may be the only treatment for tumor recurrence following liver resection, although, since the counts of WBCs and PLTs are lower, these treatments would consequently be delayed. Hypersplenism and splenomegaly for liver cancer patients may be treated with minimally invasive surgery, such as partial splenic embolization, splenic irradiation and percutaneous injection of ethanolamine oleate, although these treatments are often associated with limitations and high complications (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%